Gravity Probe B data analysis: II. Science data and their handling prior to the final analysis. (17th November 2015) - Silbergleit, A S; Conklin, J W; Heifetz, M I; Holmes, T; Li, J; Mandel, I; Solomonik, V G; Stahl, K; P W Worden Jr,; Everitt, C W F; Adams, M; Berberian, J E; et al.
Abstract: The results of the Gravity Probe B relativity science mission published in Everitt et al (2011 Phys. Rev. Lett. 106 221101 ) required a rather sophisticated analysis of experimental data due to several unexpected complications discovered on-orbit. We give a detailed description of the Gravity Probe B data reduction. In the first paper (Silbergleit et al Class. Quantum Grav. 22 224018 ) we derived the measurement models, i.e., mathematical expressions for all the signals to analyze. In the third paper (Conklin et al Class. Quantum Grav. 22 224020 ) we explain the estimation algorithms and their program implementation, and discuss the experiment results obtained through data reduction. This paper deals with the science data preparation for the main analysis yielding the relativistic drift estimates.